Temperature Effect on Formation of Polycyclic Aromatic Hydrocarbons in Acetylene Pyrolysis. Issue 34 (7th September 2022) - Gao, He; Tang, Hao
Abstract: The detailed chemical reaction mechanism of high temperature pyrolysis is constructed through the comparison of various current reaction mechanisms and sub‐models. This mechanism can better predict the formation of polycyclic aromatic hydrocarbons. Through path analysis, the interrelationship of the growth mechanisms of polycyclic aromatic hydrocarbons is expounded. And the important contribution pathways of five‐membered/six‐membered rings at high temperatures are investigated. Through component flux analysis and sensitivity analysis, the results show that the main formation path of the external five‐membered ring is the acetylene addition of naphthalene. Its stability decreases with increasing temperature and is the main introduction route of molecular curvature during low temperature pyrolysis. However, the embedded five‐membered ring obtained by benzene cycloaddition is less affected by temperature and is the most important chemical reaction process introduced by high temperature molecular curvature. The hydrogen abstraction acetylene addition mechanism still plays a dominant role at different temperatures and is a classical pathway for the formation of six‐membered rings. By cooperating with multiple reaction mechanisms, the formation mechanism of polycyclic aromatic hydrocarbons at different temperatures can be well predicted. Abstract : We report a new detailed chemical reaction mechanism of acetylene pyrolysis, which has a better ability to predict the acetylene pyrolysis process. The important paths of five‐membered/six‐membered ring structures during acetylene pyrolysis are given. High temperature is more conducive to the formation of six‐membered rings while five‐membered rings are usually stable at medium temperature.